Chapter Tracciare la rotta per iscrivere i servizi ecosistemici nella pianificazione bioregionale - Poli, Daniela (Territori, 2020)
Although still in a provisional form, as befits a field of study still undergoing consolidation, the text tries to summarize the results that emerged from the contributions collected in the volume and from their comparison; outlining, even before real conclusions, a series of clues, cues and problematic issues with which scientific reflection will have to face in the near future. Therefore, they are to be read as many beginnings of research paths, to be followed towards a plausible way of including ecosystem services in the bioregional planning of the territory.